Nostalgia Proneness and the Collective Self - Abakoumkin, Georgios; Wildschut, Tim; Sedikides, Constantine (Frontiers in Psychology, 2020)
In two studies, we examined the association between nostalgia proneness (i.e., trait-level nostalgia) and importance of the collective self. In Study 1, we tested and supported the hypothesis that nostalgia proneness is positively correlated with relational collectivism, which entails an emphasis on one’s connections with close others and small social networks. In Study 2, we demonstrated that nostalgia proneness is also positively correlated with group collectivism, which emphasizes one’s membership in more abstract, larger social groups or categories, and was reflected in increased identification with a national ingroup. These findings offer insight into the nature of nostalgia proneness—a consequential and stable personality trait.